2014
DOI: 10.1155/2014/168401
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Adenomas of the Parapharyngeal Space

Abstract: Background. Parapharyngeal space is one of potential facial planes for neoplasms and infections and represents less than 1% of all head and neck tumours. Occurrence of the pleomorphic adenoma in the parapharyngeal space is a rarity. Case Presentation. Here, three giant pleomorphic adenomas of different sizes occupying the parapharyngeal space in three patients are reported. Extensive preoperative diagnostic workup was done in order to verify the nature and size of the tumour and the proximity to the large vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…For this reason, tumors deep in the parotid gland can present as parapharyngeal masses. 2 In diagnostic workup complete blood count done, followed by fine needle aspiration cytology (FNAC), computerized tomography (CT), and magnetic resonance imaging (MRI) studies to determine the extent of disease, local spread, and even the type of tumour. MRI has been shown to be superior to computed tomography in the investigation of parapharyngeal space tumours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, tumors deep in the parotid gland can present as parapharyngeal masses. 2 In diagnostic workup complete blood count done, followed by fine needle aspiration cytology (FNAC), computerized tomography (CT), and magnetic resonance imaging (MRI) studies to determine the extent of disease, local spread, and even the type of tumour. MRI has been shown to be superior to computed tomography in the investigation of parapharyngeal space tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The main structures contained in anterior compartment include the pterygoid and tensor palatni muscles, fat and deep lobe of the parotid gland. 2 Parapharyngeal space may become involved by various infectious, inflammations, and neoplasms in head and neck. Both benign and malignant tumors may arise from any structure contained within the PPS where 70-80% appears to be benign and 20-30% appears to be malignant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The smaller the salivary gland that is affected, the more likely it is to trigger a malignant tumour. 10 The diagnostic work-up begins with haematologic and serologic tests followed by imaging 6 . MRI provides precise information about tumour margins as well as the relationship with the surrounding structures.…”
mentioning
confidence: 99%
“…4 Spiro in his study of 2078 patients with salivary gland neoplasia reported that 20-40% of all salivary gland tumours arise from minor salivary glands, mostly from the palate (42.63%), lip (10%), buccal mucosa (5.5%), retromolar area (0.7%) as well as floor of the mouth, tongue, tonsil, pharynx and nasal cavity. [5][6][7][8][9] In rare occasions, obstructive sleep apnoea is a result of anatomical abnormalities such as a mass in the upper aerodigestive tract. Apart from obstructive sleep apnoea, tumours of this location may also cause dyspnoea, dysphagia and airway obstruction.…”
mentioning
confidence: 99%